Book Reviews - Sutherland, John F.; Lewis, Thomas T.; Swain, Martha H.; Joyce, Davis D.; Sokolow, James A.; O’Toole, Thomas; Kuzirian, Eugene E.; Schmeller, Helmut J.; Davis, Clarence B.; Susskind, Jacob L.; et al. (Teaching History: A Journal of Methods, 1981)
James Stuart Olsen. The Ethnic Dimension in American History. New York: St. Martin’s Press, 1979. Pp. xxv, 440:- Cloth, 14.95; paper, 7.95; A. C. Hepburn, ed. Minorities in History. New York: St. Martin’s Press, 1979. Pp. 251 . Cloth, 27.50. Review by John F. Sutherland of Manchester (Connecticut) Community College. David Burner, Eugene Genovese, and Forrest McDonald. The American People. St. James, New York: Revisionary Press, 1980. Cloth, 20.95; paper, 16.95. Review by Thomas T. Lewis of Mount Senario College. Richard E. Beringer. Historical Analysis: Contemporary Approaches to Clio’s Craft. New York: John Wiley and Sonds, 1978. Pp. xii, 317. Paper, 12.95. Review by Martha H. Swain of Texas Woman’s University. John T. Marcus. Sub Specie Historiae: Essays in the Manifestation of Historical and Moral Consciousness. Cranbury, New Jersey: Associated University Presses, 1980. Pp. 325. Cloth, 22.50. Review by David D. Joyce of The University of Tulsa. A. K. Dickinson and P. J. Lee. History Teaching and Historical Understanding. Exeter, New Hampshire: Heinemann Educational Books, Inc., 1978 . Pp. viii, 176. Paper, 10.95. Review by Jayme A. Sokolow of Texas Tech University. Richard W. Hull. Modern Africa: Change and Continuity. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1980. Pp. xii, 274. Paper, 9.95. Review by Thomas O’Toole of Western Carolina University. Clayton Roberts and David Roberts. A History of England. 2 volumes. Englewood Cliffs, New Jersey: Prentice-Hall, 1980. Pp. 891. Paper, 13.95 per volume. Review by Eugene E. Kuzirian of The University of Texas at El Paso. Alex de Jonge. The Weimar Chronicle: Prelude to Hitler. New York: New American Library, 1978 . Pp . 256 . Paper, 5.95. Review by Helmut J. Schmeller of Fort Hays State University. A. J. P. Taylor. The War Lords. New York: Penguin Books, 1976. Pp. 189. Paper, 3.95. Review by Clarence B. Davis of The College of Charleston. History Broadsheets. Exeter, New Hampshire: Heinemann Educational Books, 1978, 1979. 5.00 per packet. Review by Jacob L. Susskind of The Pennsylvania State University/ The Capitol Campus. Robert L. Heilbroner. The Economic Transformation of America. New York: Harcourt, Brace, Jovanovich, 1977. Pp. 276. Paper, 9.95; Henry C. Dethloff. Americans and Free Enterprise. Englewood Cliffs, New Jersey: Prentice-Hall, 1979. Pp, 336. Cloth, 13.95; Susan Previant Lee and Peter Passell. A New Economic View of American History. New York: W. W. Norton, 1979. Pp. 410. Cloth, 18.95; paper, 9.95; Martin L. Primack and James F. Willis. An Economic History of the United States. Menlo Park, Carlifornia: The Benjamin Cummings Publishing Company, 1980. Pp. 462. Cloth. 16.95. Review by William L. Downard of Saint Joseph’s College, Indiana. John Chester Miller. The Wolf by the Ears: Thomas Jefferson and Slavery. New York: New American Library, 1977. Pp. xiv, 323. Paper, 5.95. Review by Larry R. Morrison of Virginia Polytechnic Institute & State University. Edmund Morris. The Rise of Theodore Roosevelt. New York: Ballantine Books, 1979. Pp. 886. Paper, 8.95. Review by Marvin Reed of Collegeville, Pennsylvania. Ellis W. Hawley. The Great War and the Search for Modern Order: A History of the American People and Their Institutions, 1917-1933. New York: St. Martin’s Press, 1979. Pp. xvi, 264. Cloth, 12.95; paper, 4.95; Gerald D. Nash. The Great Depression and World War II: Organizaing America, 1933-1945. New York: St. Martin’s Press, 1980. Pp. xvi, 1976. Clotch, 12.95; paper, 4.95. Review by Howard W. Smith of Spring Hill College. William L. Griffen and John Marciano. Teaching the Vietnam War. Montclair, New Jersey: Allanheld, Osmun, 1979. Pp. xx, 183. Paper, 6.50. Review by Frank J. Rader of SUNY Empire State College. Michael V. Namorato, ed. Have We Overcome? Race Relations Since Brown. Jackson, Mississippi: University Press Of Mississippi, 1979. Pp. xix, 232. Cloth, 15.00; paper, 7.95. Review by Gary J. Hunter of Glassboro State College.